Uncovering the biodiversity and biosynthetic potentials of rare actinomycetes - Chijioke E. Ezeobiora; Nwamaka H. Igbokwe; Dina H. Amin; Nkechi V. Enwuru; Chiamaka F. Okpalanwa; Udoma E. Mendie (SpringerOpen, 2022)
Abstract Background Antibiotic resistance is on the rise, and new antibiotic research has slowed in recent years, necessitating the discovery of possibly novel microbial resources capable of producing bioactive compounds. Microbial infections are gaining resistance to existing antibiotics, emphasizing the need for novel medicinal molecules to be discovered as soon as possible. Because the possibilities of isolating undiscovered actinomycetes strains have decreased, the quest for novel products has shifted to rare actinomycetes genera from regular environments or the identification of new species identified in unusual habitats. Main body of the abstract The non-streptomyces actinobacteria are known as rare actinomycetes that are extremely difficult to cultivate. Rare actinomycetes are known to produce a variety of secondary metabolites with varying medicinal value. In this review, we reported the diversity of rare actinomycetes in several habitat including soil, plants, aquatic environment, caves, insects and extreme environments. We also reported some isolation methods to easily recover rare Actinobacteria from various sources guided with some procedures to identify the rare Actinobacteria isolates. Finally, we reported the biosynthetic potential of rare actinomycetes and its role in the production of unique secondary metabolites that could be used in medicine, agriculture, and industry. These microbial resources will be of interest to humanity, as antibiotics, insecticides, anticancer, antioxidants, to mention but a few. Short conclusion Rare actinomycetes are increasingly being investigated for new medicinal compounds that could help to address existing human health challenges such as newly emerging infectious illnesses, antibiotic resistance, and metabolic disorders. The bioactive secondary metabolites from uncommon actinomycetes are the subject of this review, which focuses on their diversity in different habitats, isolation, identification and biosynthetic potentials.